2019
DOI: 10.1200/jco.2019.37.7_suppl.649
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immunotherapy (IO) on primary renal tumor in metastatic renal cell cancer (mRCC).

Abstract: 649 Background: Recent data showed that cytoreductive nephrectomy (CN) should not be performed prior to systemic therapy in intermediate and poor risk groups. Immune checkpoint inhibitors (ICI) are now approved in first and second line in mRCC, but ICI effect on the primary tumor is unknown. Methods: All patients (pts) treated with ICI for mRCC without prior CN were retrospectively collected and sequential computed tomography (CT) scan evaluated for response. Primary objective was Objective Response Rate (ORR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We identified 14 studies that have addressed the effect of immunotherapy on the primary tumour in patients with metastatic RCC, where treatment was given with palliative intent [31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The studies included a variety of treatment combinations: single agent immunotherapy [2], dual immunotherapy [6], and immunotherapy in combination with VEGFR-TKIs [2].…”
Section: Effect Of Immunotherapy On the Primary In The Metastatic Set...mentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 14 studies that have addressed the effect of immunotherapy on the primary tumour in patients with metastatic RCC, where treatment was given with palliative intent [31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The studies included a variety of treatment combinations: single agent immunotherapy [2], dual immunotherapy [6], and immunotherapy in combination with VEGFR-TKIs [2].…”
Section: Effect Of Immunotherapy On the Primary In The Metastatic Set...mentioning
confidence: 99%
“…Nine studies reported data on radiological response in the primary tumour [32,33,36,[39][40][41][42][43][44]. All defined a partial response in the primary tumour (PR-primary) as ≥ 30% reduction in size from baseline.…”
Section: Radiological Response Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation